Method for removing ash from polyolefin organic solution
By using polymer aluminum chloride or bentonite as ash removal agent, the adsorption complexation reaction removes the ash in the organic polyolefin solution, solving the problem of ash affecting material performance, and achieving improvement in material performance and expansion of application scope.
Patent Information
- Application Number
- CN202510258452.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-06
- Publication Date
- 2025-04-01
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the production process of polyolefin elastomers, the presence of ash not only affects the mechanical properties and processing properties of the material, but also limits its scope of application and use value. It is difficult for the prior art to effectively remove catalysts and other metal ions.
Polyaluminum chloride or bentonite is used as ash removal agent to remove ash such as metal ions and inorganic salts in the polyolefin organic solution through adsorption and complexation reaction.
It effectively improves the volume resistivity and mechanical properties of polyolefin elastomers, reduces the residual ash content, and expands the scope of application of materials.
Smart Images

Figure CN119735722A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polyolefin production technology, and in particular relates to a method for removing ash from a polyolefin organic solution. Background Art
[0002] As an important material, polyolefin not only plays an important role in daily life, but also plays an important role in industry, science and technology. In the production process of polyolefin elastomers, ash content is one of the important factors affecting the performance of polyolefin elastomers. Ash content will not only affect the mechanical properties of polyolefin elastomers themselves, reduce their tensile strength, toughness and other indicators, and make polyolefin elastomers more prone to breakage, but also affect the processing performance of polyolefin elastomers. In the process of extrusion, injection molding and other processing, it will lead to unstable melt flow, pressure fluctuations, increase processing difficulty and reduce production efficiency. This seriously limits the scope of application and use value of polyolefin elastomers. For this reason, removing ash from polyolefin elastomers during the production process is a very important production process.
[0003] In the production process of polyolefin elastomers, flash evaporation at high temperature (250℃-350℃) is generally used to remove ash, but this is mainly for additives that may be introduced in the traditional production process. For the late transition metal nickel diimide catalytic system, polyolefin elastomers are generally produced by solution polymerization. In solution polymerization, the polyolefin elastomer will be completely dissolved in the reaction solvent, and the catalyst molecules will be tightly combined with or embedded in the polyolefin elastomer chain segments, which increases the difficulty of removing the catalyst by physical methods (such as flash evaporation, filtration, etc.). Furthermore, for the late transition metal nickel diimide catalytic system, the nickel diimide catalyst is usually more stable and temperature resistant, which means that it cannot be easily completely removed from the polyolefin organic solution by flash evaporation. At the same time, the co-catalyst introduced in the production process and the antioxidants, light stabilizers, etc. added to improve the product performance will also cause the polyolefin organic solution to contain additional metal ions and inorganic components, increasing the ash content in the polyolefin organic solution. Summary of the invention
[0004] In view of the above technical problems, the present invention provides a method for removing ash from a polyolefin organic solution, in order to at least partially solve the above technical problems. The specific technical solutions provided by the present invention are as follows.
[0005] The present invention provides a method for removing ash from a polyolefin organic solution, comprising: contacting an ash removing agent with the polyolefin organic solution so that the ash in the polyolefin organic solution is removed by adsorption and complexation of the ash removing agent; separating the deashed polyolefin organic solution from the ash removing agent to obtain a purified polyolefin organic solution; wherein the ash removing agent comprises at least one of polyaluminium chloride and bentonite.
[0006] In an embodiment of the present invention, the method for removing ash from a polyolefin organic solution provided by the present invention, since polyaluminium chloride or bentonite is insoluble in an organic solvent, polyaluminium chloride or bentonite is used to adsorb and complex ash such as metal ions and inorganic salts in the polyolefin organic solution, and polyaluminium chloride or bentonite is separated from the polyolefin organic solution, thereby removing ash from the polyolefin organic solution, and finally obtaining a polyolefin elastomer. Among them, when the ash from the polyolefin organic solution is removed by polyaluminium chloride, the linear structure of polyaluminium chloride adsorbs and complexes ash such as metal ions and inorganic salts in the polyolefin organic solution to form a highly charged polymeric ring chain body, and removes ash from the polyolefin organic solution through highly charged neutralization and bridging. Even if the distance between the two polyaluminium chloride colloid particles is far, the polymer substance can also rely on the adsorption force between the colloid particles for adsorption and bridging. Due to the bridging effect, the volume between the colloid particles becomes larger, and flocculation is gradually achieved, and the polyaluminium chloride and the polyolefin organic solution are separated to remove the ash from the polyolefin organic solution. At the same time, the flocculant with metal salts will hydrolyze and produce precipitation. During the precipitation process, the flocculant will adsorb the metal ions and inorganic salts in the polyolefin organic solution, and achieve sedimentation together, and finally obtain the polyolefin elastomer. When the ash in the polyolefin organic solution is removed by bentonite, there is a mutual replacement phenomenon of cations such as Al and Mg inside the bentonite crystal. When the cations in the bentonite crystal are replaced by other low-valent cations, the bentonite crystal itself will increase the negative charge, and then the cations adsorbed between the layers will compensate, thereby forming a large negative ion. Based on this electrical neutralization effect, the bentonite crystal has the ability to adsorb certain cations, and the adsorbed cations can exchange with the cations in the polyolefin organic solution, adsorb the metal ions and inorganic salts in the polyolefin organic solution, and finally obtain the polyolefin elastomer. After removing the ash, the volume resistivity and mechanical properties of the polyolefin elastomer are effectively improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0007] Figure 1 It is a schematic diagram of a process for removing ash from a polyolefin organic solution by a water washing removal method according to an embodiment of the present invention;
[0008] Figure 2 The figure is a schematic diagram of a process for removing ash from a polyolefin organic solution by a column separation method in another embodiment of the present invention. DETAILED DESCRIPTION
[0009] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments and with reference to the accompanying drawings.
[0010] In view of the problems of high ash content in existing polyolefin organic solutions, difficulty in removing catalysts remaining in the solutions, and difficulty in removing the color of the solutions, the present invention attempts to use polyaluminum chloride or bentonite to adsorb ash such as metal ions and inorganic salts in polyolefin organic solutions, and further provides a method for removing ash from polyolefin organic solutions. This treatment method can, on the one hand, adsorb ash in polyolefin organic solutions, and on the other hand, improve the performance of polyolefin elastomers.
[0011] Specifically, the present invention provides a method for removing ash from a polyolefin organic solution, comprising: contacting an ash removing agent with a polyolefin organic solution, so that the ash in the polyolefin organic solution is removed by adsorption and complexation of the ash removing agent; separating the polyolefin organic solution after the ash is removed from the ash removing agent to obtain a purified polyolefin organic solution; wherein the ash removing agent includes at least one of polyaluminium chloride and bentonite.
[0012] In the embodiment of the present invention, the method for removing ash from a polyolefin organic solution provided by the present invention, since polyaluminium chloride or bentonite is insoluble in an organic solvent, polyaluminium chloride or bentonite is used to adsorb and complex ash such as metal ions and inorganic salts in the polyolefin organic solution, and polyaluminium chloride or bentonite is separated from the polyolefin organic solution, thereby removing ash from the polyolefin organic solution, and finally obtaining a polyolefin elastomer. Due to the removal of ash, the volume resistivity and mechanical properties of the polyolefin elastomer are effectively improved.
[0013] According to an embodiment of the present invention, the organic solvent in the polyolefin organic solution is an alkyl solvent. The polyaluminium chloride is white polyaluminium chloride. Polyaluminium chloride is often used as a sewage flocculant, but is rarely used as a flocculant in an organic solution system. It has a wide variety of forms, including solid and liquid, and white, light yellow and brown in color. In the present invention, white polyaluminium chloride is selected, which has a higher purity, a stronger adsorption effect, and will not bring other colors to the polyolefin elastomer. Bentonite is generally white or light yellow, and may also be light grey, light green, brown-red, grey-black, etc. depending on the iron content. In the present invention, activated white clay or natural bleaching earth is preferred, and natural bleaching earth is more preferred.
[0014] In the embodiments of the present invention, polyaluminium chloride not only has strong adsorption selectivity, but also has the phenomenon of multi-layer adsorption during the adsorption process. In the early stage of chemical adsorption, the active sites on the surface of polyaluminium chloride form chemical bonds with the ash in the polyolefin organic solution, but as the adsorption proceeds, adsorption will continue to occur on the adsorbed ash. This is because the adsorbed ash will change the chemical environment on the surface of polyaluminium chloride, making it easier for subsequent ash to interact with polyaluminium chloride. For example, in the adsorption process of polyolefin organic solvent, after polyaluminium chloride adsorbs the first layer of ash, these ashes will serve as new adsorption sites to promote the adsorption of the second layer or even more layers of ash, but the adsorption force of the subsequent adsorption layer is usually weaker than the first layer. Polyaluminium chloride is used to conduct electrical neutralization adsorption and adsorption bridging complexation of metal ions and inorganic salts in the polyolefin organic solution. At the same time, polyaluminium chloride has strong selectivity in the chemical adsorption process. This is because chemical adsorption is based on the formation of chemical bonds. The aluminum atoms of polyaluminium chloride have empty orbits, and they tend to react chemically with molecules or ions with lone pairs of electrons and adsorb them. They have a good adsorption effect on some compounds containing functional groups such as hydroxyl (-OH) and amino (-NH2). This selective adsorption makes polyaluminium chloride play an important role in many separation and purification processes.
[0015] For bentonite, the hydroxyl (-OH) groups on the surface of bentonite can react with metal ions or other ions. There are exposed hydroxyl groups on the edges of the silicon-oxygen tetrahedron and aluminum-oxygen octahedron on the surface of montmorillonite particles. These hydroxyl groups can undergo protonation or deprotonation reactions under certain conditions. For example, in an acidic environment, the surface hydroxyl groups may be protonated to form -OH 2+ , which can then react with anions such as Cl - 、SO4 2- In an alkaline environment, the surface hydroxyl groups can react with metal cations (such as Zn 2+ Cr 3+ etc.) the following reaction occurs: M n+ +m(-OH) M(OH) m (n-m)+ (where M represents metal ions, n is the charge number of the metal ion, and m is the number of hydroxyl groups involved in the reaction). In this way, the metal ions are adsorbed on the surface of bentonite.
[0016] According to an embodiment of the present invention, the method for removing ash from the polyolefin organic solution of the present invention by adsorption and complexation of an ash removal agent is a water washing removal method or a column separation method, wherein the ash removal agent includes at least one of polyaluminium chloride and bentonite. When the water washing removal method is used, the polyaluminium chloride can be selected as a solid or a liquid; when the column separation method is used, the polyaluminium chloride is a solid. The specific method can be selected according to the user's choice.
[0017] According to an embodiment of the present invention, the water washing and removal method comprises: mixing and stirring a polyolefin organic solution with an aqueous ash removal agent to perform a contact operation, wherein the aqueous ash removal agent comprises an aqueous solution of polyaluminum chloride or a bentonite hydrogel; and performing two-phase separation of the polyolefin organic solution after deashing and the aqueous ash removal agent to obtain a purified polyolefin organic solution. In the water washing and removal method, the ash removal agent is dissolved in water to form an aqueous solution or dispersed in water to form a hydrogel solution, and is difficult to dissolve in an organic solvent. Therefore, when the ash removal agent adsorbs and complexes the ash in the polyolefin organic solution, the aqueous ash removal agent and the polyolefin organic solution are separated into two phases according to the immiscibility of water and the alkyl solvent. At this time, the ash is adsorbed and complexed by the ash removal agent so as to remain in the aqueous phase rather than the organic phase, thereby achieving the effect of removing ash.
[0018] In an embodiment of the present invention, polyaluminium chloride will produce a large number of positively charged ions after being dissolved in water, and these ions will be adsorbed to the surface of negatively charged particles, neutralizing the partial charge of the particles, reducing the electrostatic repulsion between the particles, making them easier to approach and adsorb to each other. At the same time, polyaluminium chloride is a high molecular polymer with a long molecular chain. When it is put into water, some groups on the molecular chain will be adsorbed on different particle surfaces, just like a "bridge" built between the particles, connecting multiple particles together to form a larger floc. The linear structure of polyaluminium chloride is used to adsorb and complex the ash such as metal ions and inorganic salts in the polyolefin organic solution. Even if the distance between the two colloid particles is far, the polymer substance can also rely on the adsorption force between the colloid particles for adsorption and bridging. The volume between the colloid particles increases due to the bridging effect, and flocculation is gradually achieved. The polyaluminium chloride aqueous solution and the polyolefin organic solution are separated to remove the ash in the polyolefin organic solution. At the same time, the flocculant with metal salts will be hydrolyzed to produce precipitation. The flocculant will adsorb other particles in the polyolefin organic solution during the precipitation process and achieve sedimentation together.
[0019] Bentonite can be dispersed into a gel in water. This hydrogel solution has a strong cation exchange capacity and a certain adsorption capacity for various gases, liquids, and organic substances. In the present invention, organic bentonite is selected, and its gel state can effectively adsorb colored ions. Bentonite, as a clay mineral with a 2:1 layer structure, is composed of two layers of SiO4 tetrahedron layers sandwiched by one layer of Al-O6 octahedron to form a basic structural unit layer, wherein Al can be replaced by Mg or Fe. Since Si-O4 tetrahedrons are partially replaced by Al-O4 tetrahedrons, when a Si atom is replaced by an Al atom, since Al has one less positive charge, this structural unit layer will generate excess negative charge, resulting in electrostatic imbalance within the structural unit layer, thereby introducing Ca with positive charge and larger radius between the layers. 2+ Mg 2+ 、Na+ The cations in the interlayer balance the excess negative charges in the structural unit layer through long-range electrostatic balance. Although these interlayer cations are at a certain distance from the location where the negative charges are generated in the structural unit layer, their positive charges can attract each other with the excess negative charges in the structural unit layer, thereby achieving the electrostatic balance of the entire structure on a macroscopic level, allowing bentonite to exist stably. The interaction between these cations and the structural unit layer is weak, making the interlayer cations exchangeable. The strong hydration of these interlayer cations also adsorbs a large number of water molecules between the layers. The ionization in the aqueous solution makes the structural unit interlayer negatively charged. The edges of the structural unit are positively charged due to the breakage of Si-O bonds and Al-O bonds. Bentonite has fine grains and a large specific surface area. At the same time, due to the weak interlayer interaction, the interlayer can be peeled, expanded, and separated into thinner single crystals under the action of the solvent, which gives bentonite a large internal surface area. Therefore, the charge and large specific surface area make bentonite highly adsorbable.
[0020] According to an embodiment of the present invention, when the polyolefin organic solution is mixed and stirred with the aqueous ash removal agent, it is carried out in a sealed container, and it is necessary to ensure that the water in the aqueous ash removal agent does not volatilize excessively during the ash removal process, and to ensure that the polyolefin organic solution is in a flowing state, so the stirring temperature is 20-200°C, for example, it can be 20°C, 60°C, 100°C, 150°C, 200°C, etc. The mass fraction of the ash removal agent in the aqueous ash removal agent is 0.1%-20%, for example, it can be 0.1%, 5%, 10%, 15%, 20%, etc. The volume ratio of the aqueous ash removal agent to the polyolefin organic solution is 1:1-1:20, for example, it can be 1:1, 1:5, 1:10, 1:15, 1:20, etc., preferably 1:1-1:10. The further increase in the mass fraction of the ash removal agent does not enhance the ash removal effect, but instead leads to an increase in cost.
[0021] Temperature has a relatively important influence on the chemical adsorption of polyaluminium chloride. The chemical adsorption process is usually accompanied by the absorption or release of heat. At low temperatures (<20°C), the chemical adsorption rate of polyaluminium chloride is slow because the molecular movement speed is slow, and the ash has less chance to contact the active sites on the surface of polyaluminium chloride. As the temperature rises, the molecular movement intensifies, the ash can more easily reach the adsorption site of polyaluminium chloride, and the adsorption rate will accelerate. However, when the temperature is too high (>200°C), the opposite situation will occur, because too high a temperature will cause the chemical bonds that have been formed to break, causing the adsorption amount to decrease. Therefore, in the process of using polyaluminium chloride to adsorb ash, appropriately increasing the temperature can improve the adsorption efficiency, but if the temperature is too high, the adsorbed ash will re-desorb. Hydrogen bonds can be formed between the hydroxyl groups on the surface of bentonite and certain organic or inorganic molecules. When molecules containing molecules that can form hydrogen bonds with hydroxyl groups (such as some organic compounds containing strong electronegative atoms such as nitrogen, oxygen, and fluorine) are close to the surface of bentonite, hydrogen bond adsorption will occur. The formation and destruction of hydrogen bonds are affected by environmental factors such as temperature and humidity. When the temperature rises, hydrogen bonds are easily destroyed and the adsorption capacity will decrease accordingly.
[0022] According to an embodiment of the present invention, the column separation method comprises: passing the polyolefin organic solution through a solid column filled with ash removal agent particles to perform contact and separation operations to obtain a purified polyolefin organic solution. The ash removal agent particles include polyaluminium chloride or bentonite particles, and the particle size of the ash removal agent particles is 50-200 mesh, for example, 50 mesh, 100 mesh, 150 mesh, 200 mesh, etc. In the column separation method, during the process of the polyolefin organic solution passing through the solid column filled with ash removal agent particles, the ash in the polyolefin organic solution is adsorbed and complexed by the ash removal agent, and when the polyolefin organic solution flows out of the solid column, the ash is retained on the ash removal agent in the solid column, thereby achieving the effect of removing ash.
[0023] According to an embodiment of the present invention, the volume of the ash removal agent particles in the solid column filled with ash removal agent particles is 10%-80% of the volume of the solid column, for example, it can be 10%, 20%, 30%, 50%, 80%, etc. The solid column is also filled with auxiliary materials, and the auxiliary materials include any one of ball rings and ceramic balls. Among them, the size of the ceramic ball is 3-5mm. The mass of the auxiliary material is 1-50% of the mass of the ash removal agent particles filled in the solid column, for example, it can be 1%, 5%, 10%, 30%, 50%, etc. Adding ball rings or ceramic balls can increase the dispersion of the ash removal agent in the solid column, which is beneficial to the flow of the polyolefin organic solution, increases the contact area between the polyolefin organic solution and the ash removal agent, and improves the ash removal effect.
[0024] According to an embodiment of the present invention, when the polyolefin organic solution passes through a solid column filled with ash removal agent particles, it is also necessary to maintain the fluidity of the polyolefin organic solution. Therefore, the temperature is set to 60-200°C, for example, 60°C, 100°C, 120°C, 150°C, 200°C, etc. When the ash removal agent is polyaluminum chloride, it is preferably 60-120°C, and when the ash removal agent is bentonite, it is preferably 20-90°C; the pressure is 0.1-2MPa, for example, 0.1MPa, 0.5MPa, 1MPa, 1.5MPa, 2MPa, etc., preferably 0.1-1MPa. Applying a certain pressure is conducive to sufficient contact between the polyolefin organic solution and the ash removal agent.
[0025] According to an embodiment of the present invention, the polyolefin organic solution is obtained by the following method: adding a comonomer, a main catalyst and a co-catalyst into an alkyl solvent to carry out a polymerization reaction to obtain a polyolefin organic solution; or dissolving the polyolefin to be purified in an alkyl solvent to obtain a polyolefin organic solution.
[0026] According to an embodiment of the present invention, the alkyl solvent includes one or more of ethane, isobutane, n-pentane, isopentane, n-hexane, methylcyclopentane, n-heptane, cyclohexane, methylcyclohexane, isooctane, and toluene, preferably n-hexane, methylcyclopentane, n-heptane, and more preferably n-hexane and n-heptane. The comonomer includes one or more of ethylene, propylene, and butene; the main catalyst includes α-diimine nickel; the cocatalyst includes one or more of diethylaluminum chloride, trimethylaluminum, triethylaluminum, triisobutylaluminum, triethylaluminum trichloride, and methylaluminoxane. The temperature of the polymerization reaction is 40-120°C, for example, 40°C, 80°C, 100°C, 120°C, etc. The time of the polymerization reaction is 10-60min, for example, 10min, 20min, 30min, 50min, 60min, etc. The pressure of the polymerization reaction is 0.5-5MPa, for example, 0.5MPa, 1MPa, 3MPa, 5MPa, etc.
[0027] As an example, the present invention provides a method for removing ash from a polyolefin organic solution by water washing and removal, the specific process is as follows: Figure 1 shown.
[0028] like Figure 1As shown, firstly, the preparation of the water-containing ash removal agent includes: weighing a certain amount of ash removal agent, adding it to water, stirring it at 20-120°C and 500-6000rpm for 10-60min, and standing it for 4-12h for standby. Among them, the mass fraction of the ash removal agent is 0.1%-20%. When the ash removal agent is polyaluminum chloride, the mass fraction is preferably 0.1-5%, more preferably 0.5-2%, and most preferably 0.5%; the stirring temperature is preferably 80-120°C, more preferably 100-110°C, and most preferably 100°C. When the ash removal agent is bentonite, the mass fraction is preferably 5-20%, more preferably 10-15%, and most preferably 10%; the stirring temperature is preferably 20-100°C, more preferably 30-50°C, and most preferably 30°C; the rotation speed is preferably 1500-4500rpm, and more preferably 1500rpm. A screw-belt stirring paddle is preferably used for stirring, and a water-containing ash removal agent has a better ash removal effect.
[0029] The preparation of polyolefin organic solution comprises: adding comonomer, main catalyst and cocatalyst into alkyl solvent, carrying out polymerization reaction, and obtaining polyolefin organic solution. Among them, α-diimine nickel catalyst is selected as main catalyst, cocatalyst is one or more of diethylaluminum chloride, trimethylaluminum, triethylaluminum, triisobutylaluminum, triethylaluminum trichloride, methylaluminoxane, alkyl solvent is one or more of ethane, isobutane, n-pentane, isopentane, n-hexane, methylcyclopentane, n-heptane, cyclohexane, methylcyclohexane, isooctane, toluene, comonomer is one or more of ethylene, propylene, butene, polymerization reaction temperature is preferably 40-120°C, polymerization reaction pressure is preferably 0.5-5MPa, polymerization reaction time is preferably 10-60min.
[0030] The above polyolefin organic solution and the aqueous ash removal agent are added to the mixer at the same time, wherein the volume ratio of the aqueous ash removal agent to the polyolefin organic solution is preferably 1:1-1:20, and the stirring temperature is preferably 20-200°C. When the ash removal agent is polyaluminium chloride, the stirring temperature is preferably 80-120°C, more preferably 100°C; when the ash removal agent is bentonite, the stirring temperature is preferably 20-80°C, more preferably 60°C. Stir thoroughly for 10-120 minutes, then output to the separator; then centrifuge at 500-8000r / min to obtain a purified polyolefin organic solution. The purified polyolefin organic solution is transported to a flash tank, and the separated ash removal agent is recycled.
[0031] As another example, the present invention provides a method for removing ash from a polyolefin organic solution by column separation, the specific process is as follows: Figure 2 shown.
[0032] like Figure 2As shown, the solid column filled with ash removal agent particles includes: filling the ash removal agent with a particle size of 50-200 mesh into the solid column, and adding 1%-50% (by mass fraction of the ash removal agent) of auxiliary materials. The volume of the ash removal agent is 10%-80% of the volume of the solid column, preferably 20%-60%. The auxiliary material includes any one of a ball ring and a ceramic ball.
[0033] The preparation of polyolefin organic solution comprises: adding comonomer, main catalyst and cocatalyst into alkyl solvent, carrying out polymerization reaction, and obtaining polyolefin organic solution. Among them, α-diimine nickel catalyst is selected as main catalyst, cocatalyst is one or more of diethylaluminum chloride, trimethylaluminum, triethylaluminum, triisobutylaluminum, triethylaluminum trichloride, methylaluminoxane, alkyl solvent is one or more of ethane, isobutane, n-pentane, isopentane, n-hexane, methylcyclopentane, n-heptane, cyclohexane, methylcyclohexane, isooctane, toluene, comonomer is one or more of ethylene, propylene, butene, polymerization reaction temperature is preferably 40-120°C, polymerization reaction pressure is preferably 0.5-5MPa, polymerization reaction time is preferably 10-60min.
[0034] The above polyolefin organic solution is directly transported to the solid column of the ash removal agent, and stays for 10-60 minutes at 60-200°C and pressure of 0.1-2MPa for full contact and adsorption complexation. The outflowing polyolefin organic solution is transported to the flash tank.
[0035] The present invention is further described below by examples and related test experiments. In the detailed description below, for ease of explanation, many specific details are set forth to provide a comprehensive understanding of the embodiments of the present invention. However, it is obvious that one or more embodiments may also be implemented without these specific details. And, in the absence of conflict, the details in the following embodiments may be combined into other feasible embodiments at will. All instruments, consumables and reagents in the following examples, if not otherwise specified, may be obtained from commercial sources.
[0036] Example 1
[0037] In this embodiment 1, ash is removed from the polyolefin organic solution by water washing and removal. Specifically, in this embodiment 1, polyaluminium chloride aqueous solutions of different concentrations are prepared to remove ash from the polyolefin organic solution, and the specific steps are as follows.
[0038] First, prepare the polyaluminium chloride aqueous solution: take 1L of water, weigh a certain amount of polyaluminium chloride, prepare polyaluminium chloride aqueous solutions with mass fractions of 0.1%, 0.5%, and 1%, respectively, stir thoroughly at 100°C, and set aside.
[0039] Preparation of polyolefin organic solution: α-diimine nickel catalyst was selected as the main catalyst, diethylaluminum chloride was used as the co-catalyst, heptane was used as the polymerization solvent (i.e. the above-mentioned alkyl solvent), and the polymerization reaction was carried out under an ethylene atmosphere. The polymerization reaction temperature was 60° C., the polymerization reaction pressure was 3 MPa, and the polymerization reaction time was 30 min.
[0040] The above polyolefin organic solution and different polyaluminium chloride (PAC) aqueous solutions were added into the mixer respectively, the volume ratio of polyaluminium chloride aqueous solution to polyolefin organic solution was 1:5, and they were fully stirred at 120°C for 30 minutes, then output to the separator, centrifuged at 3000r / min, and the purified polyolefin organic solution was transported to the flash tank, and the separated polyaluminium chloride was recycled.
[0041] The purified polyolefin elastomer was tested for ash content. The polyolefin elastomer that was directly flashed without removing ash and the polyolefin elastomer treated with polyaluminium chloride were tested for ash content. The ash content was tested according to GB / T 9345.1-2008, the transmittance was tested according to GB / T 2410-2008, the tensile strength was tested according to GB / T 1040.3-2006, and the volume resistivity was tested according to GB / T 31838.2-2019. The test results are shown in Table 1.
[0042] Specifically, the ash content was tested by the following method.
[0043] The test equipment includes: Crucible, quartz crucible, ceramic crucible, platinum crucible that does not react chemically with the sample to be tested. Muffle furnace or microwave oven, which can control the calcination temperature within 600±25℃, 750±50℃, 850±50℃ or 950±50℃ during calcination. Analytical balance, with a graduation value of 0.1mg. Desiccator, containing high-efficiency desiccant that does not react with ash.
[0044] The test principle involves burning the sample to be tested and calcining the residue at high temperature (300-1000°C) to constant weight.
[0045] Sampling volume: The sample to be tested should be sufficient to produce 5-50 mg of ash. If the approximate ash content is unknown in advance, a pre-determination is required. For samples with very little ash, the sampling volume must be increased.
[0046] Specific operation steps: Place the crucible in a Muffle furnace and heat it at a test temperature of 150°C for 3 hours to constant weight. Transfer it to a desiccator with crucible tongs for at least 1 hour, cool it to room temperature, and weigh the mass of the crucible on an analytical balance, record it, and be accurate to 0.1 mg. The volume of the crucible is sufficient, and the weighed sample to be tested is placed in the crucible and weighed, and record it. The sample to be tested is placed in the crucible, and it cannot exceed half the height of the crucible. Transfer the sample in the crucible to a Muffle furnace for calcination, set the temperature of the Muffle furnace to 300°C within 0.5h, and keep it for 0.5h; then set the temperature of the Muffle furnace to 600°C within 0.5h, and keep it for 0.5h; finally set the temperature of the Muffle furnace to 850°C within 0.5h, and keep it for 6h. Transfer the crucible that has dropped to about 100°C to a desiccator, cool it to room temperature, and test it on an analytical balance, with an accuracy of 0.1 mg. The test was performed in parallel at least twice under the same conditions, and the difference between the two weighing results should not exceed 0.5 mg.
[0047] Table 1 Test results of ash content, light transmittance and tensile strength of polyolefin elastomers treated with polyaluminium chloride aqueous solution at different concentrations
[0048]
[0049] Example 2
[0050] In this embodiment 2, ash is removed from the polyolefin organic solution by water washing and removal. Specifically, in this embodiment 2, a certain concentration of polyaluminium chloride aqueous solution is configured to remove ash from the polyolefin organic solution at different temperatures, and the specific steps are as follows.
[0051] First, prepare a 0.5% by mass aqueous solution of polyaluminium chloride, stir it thoroughly at 100°C, and set aside.
[0052] Preparation of polyolefin organic solution: α-diimine nickel catalyst was selected as the main catalyst, diethylaluminum chloride was used as the co-catalyst, heptane was used as the polymerization solvent, and the polymerization reaction was carried out in an ethylene atmosphere. The polymerization reaction temperature was 60° C., the polymerization reaction pressure was 3 MPa, and the polymerization reaction time was 30 min.
[0053] The above polyolefin organic solution and the polyaluminium chloride (PAC) aqueous solution are added into the mixer respectively, the volume ratio of the polyaluminium chloride aqueous solution to the polyolefin organic solution is 1:5, and they are fully stirred for 30 minutes at 60°C, 80°C, 100°C and 120°C respectively, and then output to the separator, centrifuged at 3000r / min, and the purified polyolefin organic solution is transported to the flash tank, and the separated polyaluminium chloride is recycled.
[0054] The purified polyolefin elastomer was tested for ash content. The polyolefin elastomer that was directly flashed without removing ash and the polyolefin elastomer treated with polyaluminium chloride were tested for ash content. The ash content was tested according to GB / T 9345.1-2008, the transmittance was tested according to GB / T 2410-2008, the tensile strength was tested according to GB / T 1040.3-2006, and the volume resistivity was tested according to GB / T 31838.2-2019. The test results are shown in Table 2.
[0055] Table 2 Ash content, light transmittance and tensile strength test results of polyolefin elastomers treated with polyaluminium chloride aqueous solution at different temperatures
[0056]
[0057] Example 3
[0058] In this embodiment 3, ash is removed from the polyolefin organic solution by water washing. Specifically, in this embodiment 3, a certain concentration of polyaluminium chloride aqueous solution is prepared at the same temperature and different stirring speeds to remove ash from the polyolefin organic solution. The specific steps are as follows.
[0059] First, prepare a 0.5% by mass aqueous solution of polyaluminium chloride, stir it thoroughly at 100°C, and set aside.
[0060] Preparation of polyolefin organic solution: α-diimine nickel catalyst was selected as the main catalyst, diethylaluminum chloride was used as the co-catalyst, heptane was used as the polymerization solvent, and the polymerization reaction was carried out in an ethylene atmosphere. The polymerization reaction temperature was 60° C., the polymerization reaction pressure was 3 MPa, and the polymerization reaction time was 30 min.
[0061] The above polyolefin organic solution and polyaluminium chloride (PAC) aqueous solution are added into a mixer with a volume ratio of polyaluminium chloride aqueous solution to polyolefin organic solution of 1:5. The mixture is stirred for 30 minutes at 100°C and then output into a separator for centrifugal separation at 500, 1500, 3000, 4500 and 6000 r / min, respectively. The purified polyolefin organic solution is transported into a flash tank and the separated polyaluminium chloride is recycled.
[0062] The purified polyolefin elastomer was tested for ash content. The polyolefin elastomer that was directly flashed without removing ash and the polyolefin elastomer treated with polyaluminium chloride were tested for ash content. The ash content was tested according to GB / T 9345.1-2008, the transmittance was tested according to GB / T 2410-2008, the tensile strength was tested according to GB / T 1040.3-2006, and the volume resistivity was tested according to GB / T 31838.2-2019. The test results are shown in Table 3.
[0063] Table 3 Ash content, light transmittance and tensile strength test results of polyolefin elastomers treated with polyaluminium chloride aqueous solution at different rotation speeds
[0064]
[0065] Example 4
[0066] In this embodiment 4, ash is removed from the polyolefin organic solution by column separation method. The specific steps are as follows.
[0067] The filling of the polyaluminium chloride solid column includes: filling the polyaluminium chloride with a particle size of 100 mesh into the solid column, and adding 30% (based on the mass fraction of the polyaluminium chloride) of ball rings, wherein the filling amounts of the polyaluminium chloride in the solid column are 20%, 40% and 60% (volume fraction of the solid column) respectively.
[0068] Filling the 3A molecular sieve solid column includes: filling the molecular sieve with a particle size of 100 mesh into the solid column, and adding 30% (based on the mass fraction of the molecular sieve) of ball rings, wherein the filling amount of the 3A molecular sieve in the solid column is 60% (volume fraction of the solid column).
[0069] The filling of the activated alumina solid column includes: filling alumina with a particle size of 100 mesh into the solid column, and adding 30% (based on the mass fraction of alumina) of ball rings, wherein the filling amount of alumina in the solid column is 60% (volume fraction of the solid column).
[0070] The preparation of polyolefin organic solution includes: selecting α-diimine nickel catalyst as main catalyst, diethylaluminum chloride as co-catalyst, heptane as polymerization solvent, carrying out polymerization reaction under ethylene atmosphere, the polymerization reaction temperature is 60° C., the polymerization reaction pressure is 3 MPa, and the polymerization reaction time is 30 min.
[0071] The above polyolefin organic solutions were respectively transported to solid columns filled with polyaluminium chloride solid, 3A molecular sieve and activated alumina, and stayed at 100°C and 0.5MPa for 30 minutes for full contact and adsorption complexation. The outflowing polyolefin organic solution was transported to a flash tank.
[0072] The purified polyolefin elastomer was tested for ash content. The polyolefin elastomer that was directly flashed without removing ash and the polyolefin elastomer treated with polyaluminium chloride were tested for ash content. The ash content was tested according to GB / T 9345.1-2008, the transmittance was tested according to GB / T 2410-2008, the tensile strength was tested according to GB / T 1040.3-2006, and the volume resistivity was tested according to GB / T 31838.2-2019. The test results are shown in Table 4.
[0073] Table 4 Test results of ash content, light transmittance and tensile strength of polyolefin elastomers treated with polyaluminium chloride at different volume fractions
[0074]
[0075] It can be seen from Tables 1 to 4 that polyaluminium chloride can effectively adsorb ash such as metal ions and inorganic salts in polyolefin organic solutions, thereby reducing the ash content in polyolefin elastomers, improving the light transmittance, mechanical properties and electrical properties of polyolefin elastomers, and has a better deashing effect than existing commercial adsorbents.
[0076] Example 5
[0077] In this embodiment 5, ash is removed from the polyolefin organic solution by water washing and removal. Specifically, in this embodiment 5, SMP-N bentonite hydrogel aqueous solution is prepared and mixed with the polyolefin organic solution in different ratios to remove ash from the polyolefin organic solution. The specific steps are as follows.
[0078] First, prepare the bentonite hydrogel aqueous solution: take 1L of water, weigh a quantitative amount of 10% SMP-N bentonite (200 mesh particle size pass rate ≥ 95%, density 2.0-2.5g / cm 2 , pH 9±1), fully stirred at 1500 rpm for 30 min at 30°C, and allowed to stand for 4 h before use.
[0079] Preparation of polyolefin organic solution: α-diimine nickel catalyst was selected as the main catalyst, diethylaluminum chloride was used as the co-catalyst, heptane was used as the polymerization solvent, and the polymerization reaction was carried out in an ethylene atmosphere. The polymerization reaction temperature was 60° C., the polymerization reaction pressure was 3 MPa, and the polymerization reaction time was 30 min.
[0080] The above polyolefin organic solutions were added to the mixer with SMP-N bentonite hydrogel in the ratio of 1:1, 5:1 and 10:1 respectively, fully stirred at 60°C for 30 minutes, then output to the separator, centrifuged at 3000r / min, and the purified polyolefin organic solution was transported to the flash tank, and the separated bentonite was recycled.
[0081] The purified polyolefin elastomer was tested for ash content. The polyolefin elastomer that was directly flashed without removing ash and the polyolefin elastomer treated with bentonite hydrogel were tested for ash content. The ash content was tested according to GB / T 9345.1-2008, the transmittance was tested according to GB / T 2410-2008, the tensile strength was tested according to GB / T 1040.3-2006, and the volume resistivity was tested according to GB / T 31838.2-2019. The test results are shown in Table 5.
[0082] Table 5 Ash content, light transmittance and tensile strength test results of polyolefin elastomers treated with SMP-N bentonite hydrogels at different ratios
[0083]
[0084] Example 6
[0085] In this embodiment 6, ash is removed from the polyolefin organic solution by water washing and removal. Specifically, in this embodiment 6, SMP-HA bentonite hydrogel aqueous solution is prepared and mixed with the polyolefin organic solution in different ratios to remove ash from the polyolefin organic solution. The specific steps are as follows.
[0086] First, prepare the bentonite hydrogel aqueous solution: take 1L of water, weigh a quantitative amount of 10% SMP-HA bentonite (200 mesh particle size pass rate ≥ 95%, density 2.0-2.5g / cm 2 , pH 9±1), fully stirred at 1500 rpm for 30 min at 30°C, and allowed to stand for 4 h before use.
[0087] Preparation of polyolefin organic solution: α-diimine nickel catalyst was selected as the main catalyst, diethylaluminum chloride was used as the co-catalyst, heptane was used as the polymerization solvent, and the polymerization reaction was carried out in an ethylene atmosphere. The polymerization reaction temperature was 60° C., the polymerization reaction pressure was 3 MPa, and the polymerization reaction time was 30 min.
[0088] The above polyolefin organic solutions were added to the mixer with SMP-HA bentonite hydrogel in the ratio of 1:1, 5:1 and 10:1 respectively, fully stirred at 60°C for 30 minutes, then output to the separator, centrifuged at 3000r / min, and the purified polyolefin organic solution was transported to the flash tank, and the separated bentonite was recycled.
[0089] The purified polyolefin elastomer was tested for ash content. The polyolefin elastomer that was directly flashed without removing ash and the polyolefin elastomer treated with SMP-HA bentonite hydrogel were tested for ash content. The ash content was tested according to GB / T 9345.1-2008, the transmittance was tested according to GB / T 2410-2008, the tensile strength was tested according to GB / T 1040.3-2006, and the volume resistivity was tested according to GB / T 31838.2-2019. The test results are shown in Table 6.
[0090] Table 6 Ash content, light transmittance and tensile strength test results of polyolefin elastomers treated with SMP-HA bentonite hydrogels at different ratios
[0091]
[0092] Example 7
[0093] In this embodiment 7, ash is removed from the polyolefin organic solution by water washing and removal. Specifically, in this embodiment 7, SMP-HA bentonite hydrogel aqueous solution is configured at different temperatures to remove ash from the polyolefin organic solution, and the specific steps are as follows.
[0094] First, prepare the bentonite hydrogel aqueous solution: take 1L of water, weigh a quantitative amount of 10% SMP-HA bentonite (200 mesh particle size pass rate ≥ 95%, density 2.0-2.5g / cm 2 , pH 9±1), fully stirred at 1500 rpm for 30 min at 30°C, and allowed to stand for 4 h before use.
[0095] Preparation of polyolefin organic solution: α-diimine nickel catalyst was selected as the main catalyst, diethylaluminum chloride was used as the co-catalyst, heptane was used as the polymerization solvent, and the polymerization reaction was carried out in an ethylene atmosphere. The polymerization reaction temperature was 60° C., the polymerization reaction pressure was 3 MPa, and the polymerization reaction time was 30 min.
[0096] The above polyolefin organic solution was added to the mixer with SMP-HA bentonite hydrogel in a ratio of 5:1, and fully stirred at 20°C, 40°C, 60°C, 80°C and 90°C for 30 minutes, respectively. Then, the solution was output to the separator and centrifuged at 3000r / min. The purified polyolefin organic solution was transported to a flash tank, and the separated bentonite was recycled.
[0097] The purified polyolefin elastomer was tested for ash content. The polyolefin elastomer that was directly flashed without removing ash and the polyolefin elastomer treated with bentonite hydrogel were tested for ash content. The ash content was tested according to GB / T 9345.1-2008, the transmittance was tested according to GB / T 2410-2008, the tensile strength was tested according to GB / T 1040.3-2006, and the volume resistivity was tested according to GB / T 31838.2-2019. The test results are shown in Table 7.
[0098] Table 7 Ash content, transmittance and tensile strength test results of polyolefin elastomers treated with SMP-HA bentonite hydrogel at different temperatures
[0099]
[0100] Example 8
[0101] In this embodiment 8, ash is removed from the polyolefin organic solution by column separation method. The specific steps are as follows.
[0102] The process of filling a solid column with bentonite ore comprises: filling bentonite with a particle size of 200 meshes into the solid column, and adding 20% (by mass fraction of bentonite) of ceramic balls, wherein the filling amounts of bentonite in the solid column are 15%, 30%, and 60% (by volume fraction of the solid column), respectively, and heating the solid column filled with bentonite to 80°C.
[0103] The filling of the 3A molecular sieve solid column includes: filling the molecular sieve with a particle size of 200 mesh into the solid column, and adding 20% (by mass fraction of the molecular sieve) of ceramic balls, wherein the filling amount of the 3A molecular sieve in the solid column is 60% (volume fraction of the solid column), and heating the solid column filled with the molecular sieve to 80°C.
[0104] The filling of the activated alumina solid column includes: filling alumina with a particle size of 200 mesh into the solid column, and adding 20% (by mass fraction of alumina) of ceramic balls, wherein the filling amount of alumina in the solid column is 60% (volume fraction of the solid column), and heating the solid column filled with alumina to 80°C.
[0105] The preparation of polyolefin organic solution includes: selecting α-diimine nickel catalyst as main catalyst, diethylaluminum chloride as co-catalyst, heptane as polymerization solvent, carrying out polymerization reaction under ethylene atmosphere, the polymerization reaction temperature is 60° C., the polymerization reaction pressure is 3 MPa, and the polymerization reaction time is 30 min.
[0106] The above polyolefin organic solutions were respectively transported to solid columns filled with bentonite, 3A molecular sieve and activated alumina, and stayed at 80°C and 0.3MPa for 20 minutes for full contact and adsorption complexation. The outflowing polyolefin organic solution was transported to a flash tank.
[0107] The purified polyolefin elastomer was tested for ash content. The polyolefin elastomer that was directly flashed without removing ash and the polyolefin elastomer treated with bentonite were tested for ash content. The ash content was tested according to GB / T 9345.1-2008, the transmittance was tested according to GB / T 2410-2008, the tensile strength was tested according to GB / T 1040.3-2006, and the volume resistivity was tested according to GB / T 31838.2-2019. The test results are shown in Table 8.
[0108] Table 8 Ash content, transmittance and tensile strength test results of polyolefin elastomers treated with bentonite at different volume fractions
[0109]
[0110] It can be seen from Tables 5 to 8 that bentonite can effectively adsorb ash such as metal ions and inorganic salts in polyolefin organic solutions, thereby reducing the ash content in polyolefin elastomers, improving the light transmittance, mechanical properties and electrical properties of polyolefin elastomers, and has better deashing effect than existing commercial adsorbents.
[0111] In summary of the above embodiments, the present invention is a deashing method for simply and efficiently removing ash from a polyolefin organic solution. The metal ions and inorganic salts in the polyolefin organic solution can be effectively adsorbed by polyaluminium chloride or bentonite, thereby significantly reducing their residual amount and improving the light transmittance, mechanical properties and electrical properties of the polyolefin elastomer.
[0112] The specific embodiments described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for removing ash from a polyolefin organic solution, characterized in that: The method comprises: contacting an ash removal agent with a polyolefin organic solution, so that ash in the polyolefin organic solution is removed by adsorption and complexation of the ash removal agent; The ash-removed polyolefin organic solution is separated from the ash-removing agent to obtain a purified polyolefin organic solution; Wherein, the ash removal agent includes at least one of polyaluminium chloride and bentonite; The polyolefin organic solution is obtained by the following method: Adding a comonomer, a main catalyst and a co-catalyst into an alkyl solvent to carry out a polymerization reaction to obtain a polyolefin organic solution; or The polyolefin to be purified is dissolved in an alkyl solvent to obtain a polyolefin organic solution.
2. The method according to claim 1, characterized in that The polyaluminium chloride is white polyaluminium chloride.
3. The method according to claim 1, characterized in that The method for removing ash from the polyolefin organic solution is a water washing removal method, which comprises: The polyolefin organic solution is mixed and stirred with a water-containing ash-removing agent to carry out the contacting operation, wherein the water-containing ash-removing agent comprises a polyaluminum chloride aqueous solution or a bentonite hydrogel; The deashed polyolefin organic solution and the aqueous ash-removing agent are separated into two phases to obtain a purified polyolefin organic solution.
4. The method according to claim 3, characterized in that When the polyolefin organic solution and the aqueous ash removal agent are mixed and stirred, the stirring temperature is 20-200° C.; The mass fraction of the ash remover in the aqueous ash remover is 0.1%-20%; The volume ratio of the aqueous ash removing agent to the polyolefin organic solution is 1:1-1:
20.
5. The method according to claim 1, characterized in that The method for removing ash from the polyolefin organic solution is a column separation method, which comprises: Passing the polyolefin organic solution through a solid column filled with ash removal agent particles to perform the contact and separation operations to obtain a purified polyolefin organic solution; Wherein, the ash removal agent particles include polyaluminium chloride or bentonite particles; The particle size of the ash removal agent particles is 50-200 meshes.
6. The method according to claim 5, characterized in that The volume of the ash removal agent particles in the solid column filled with ash removal agent particles is 10%-80% of the volume of the solid column; The solid column is also filled with auxiliary materials; The auxiliary material includes any one of a ball ring and a ceramic ball; The particle size of the ceramic balls is 3-5 mm; The mass of the auxiliary material is 1-50% of the mass of the ash removal agent particles filled in the solid column.
7. The method according to claim 5, characterized in that When the polyolefin organic solution passes through the solid column filled with ash removing agent particles, the temperature is 60-200° C. and the pressure is 0.1-2 MPa.
8. The method according to claim 1, characterized in that The alkyl solvent includes one or more of ethane, isobutane, n-pentane, isopentane, n-hexane, methylcyclopentane, n-heptane, cyclohexane, methylcyclohexane, isooctane, and toluene; The comonomer includes one or more of ethylene, propylene and butene; The main catalyst includes α-diimide nickel; The co-catalyst includes one or more of diethylaluminum chloride, trimethylaluminum, triethylaluminum, triisobutylaluminum, triethylaluminum trichloride, and methylaluminoxane; The polymerization reaction temperature is 40-120° C., the polymerization reaction time is 10-60 min, and the polymerization reaction pressure is 0.5-5 MPa.
9. The method according to any one of claims 1 to 8, characterized in that The polyolefin includes a polyolefin elastomer.
Citation Information
Patent Citations
Adsorbent for removing polar compounds in olefin as well as preparation method and application of adsorbent
CN114425296A
Polyolefin preparation method and system
CN116751325A
Preparation method of PHS resin
CN118388686A
Process for post-treatment of vinyl polymers and vinyl polymers obtained thereby
CN119219805A
Method for refining and obtaining resin-dissolved solution and method for producing chemically amplified photoresist composition
JP2010159399A